ELIMINATION OF LEGAL DEFECIENCIES OF FINAL JUDGMENTS - Miladinović Stefanović, Dušica; Кнежевић, Саша (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The final convicting verdict marks the beginning of enforcing the final court decision as stated in the formal pronouncement of the judgment passed by the court. The court verdict evolves from a thorough and meticulous factual reonstruction of the criminal act and the application of the criminal code norms on the determined facts. The institutionalized reaction to the offender’s suspected wrongdoing is crowned by the final verdict passed in the closing stages of the court proceedings.Filing an appeal against the final verdict ensures the supervision of legality and property of the verdict rendered in the first-instance proceedings. The court decision about the legal remedy is final and executive. The consequences of any deficiencies present in the final verdict may be removed only by the decision passed by a high court in the proceeding initiated by extraordinary legal remedies. The final verdict can be annulled because of its factual or legal deficiencies. This paper examines the deficiencies of the legal grounds of the final verdict.
Keywords: verdict; final verdict; legal grounds of the verdict; legal remedies; request for the protection of legality; legal deficiencies of the verdict